2007
DOI: 10.1088/0022-3727/40/6/002
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature ferroelectric, ferromagnetic and magnetoelectric properties of Ba-doped BiFeO3thin films

Abstract: Ba-doped multiferroic BiFeO3thin films were successfully prepared on Pt/TiO2/SiO2/Si(1 0 0) substrates by pulsed laser deposition. X-ray diffraction showed that the Bi0.75Ba0.25FeO3thin film was single phase with (1 0 1) preferential polycrystalline orientation. Both ferroelectricity and ferromagnetism of these films were observed at room temperature by P–E and M–H loop measurements, respectively. The magnetoelectric coupling effect was demonstrated by measuring the dielectric constant in a varying magnetic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 35 publications
0
53
0
Order By: Relevance
“…As the growing requirement for high temperature piezoelectric materials in spintronics, information storage, sensors, actuators and device used in extreme conditions, materials based on the BiFeO 3 -PbTiO 3 (BF-PT) system have drawn considerable attentions for their high Curie temperature and the coexistence of ferroelectric and ferromagnetic orderings [1][2][3][4][5][6][7]. In addition, modifications including rare earth and third phase dopants have been introduced in to improve the insulativity and decrease the internal mechanical stresses in BF-PT system [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As the growing requirement for high temperature piezoelectric materials in spintronics, information storage, sensors, actuators and device used in extreme conditions, materials based on the BiFeO 3 -PbTiO 3 (BF-PT) system have drawn considerable attentions for their high Curie temperature and the coexistence of ferroelectric and ferromagnetic orderings [1][2][3][4][5][6][7]. In addition, modifications including rare earth and third phase dopants have been introduced in to improve the insulativity and decrease the internal mechanical stresses in BF-PT system [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Room temperature magnetic hysteresis loops have been observed in BiFeO 3 doped by Sr, Eu, Gd, Ba, La, Dy, etc. [4][5][6][7][8][9]. Recently, Su et al reported the enhanced magnetic properties and large polarization in BiFeO 3 ceramic prepared by high-pressure synthesis [10], indicating the possible realization of ferromagnetism in none-doped BiFeO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…3 The most studied multiferroic systems of BiFeO 3 have low resistivity, 4 which results in weak ferromagnetism 5 and small polarization at room temperature. 6 Li et al 7 reported the low resistivity in BiFeO 3 system, i.e., dependent on oxygen vacancies, low valence Fe ion due to their nonstiochiometric behavior and incomplete charge compensation, which may effect the distortion of the lattice. Rossiter et al 8 reported that the highly resistive magnetoelectric semiconductor attributes short-range interaction between the conduction and the localized spin electrons, which are highly disordered and contribute weak superparamagnetic/paraelectric relaxation.…”
mentioning
confidence: 99%